Clearer Conceptions of Insider Preferences - Peter A. Alces (Washington University Law Quarterly, 1993)
In the midst of the falling sky, Professor Jay Westbrook offered a qualified defense of Levit.27 His defense was provocative, but seriously flawed. I wrote a Response to the Westbrook Article (Article) which identified deficiencies in his analysis and suggested that a much better case could be made for Levit.28 Westbrook then wrote a passionate Reply that was sharply critical of my Response. 29 This essay-rejoinder will put Levit, the Westbrook/Alces differences, and the consequences of our differences in perspective.
Keywords: Preferential transactions (Bankruptcy); Bankruptcy transfer avoidance